Experimental study on the seismic behavior of masonry wall-to-floor connections - Moreira, Susana Maria Trindade (2012)
The global structural performance of masonry buildings, under earthquake loading, is affected by the efficiency of wall-to-floor connections, since they assure the continuity of the energy path and prevent the occurrence of most of the local collapse mechanisms. In fact, out-of-plane behaviour of masonry walls observed in recent seismic events showed the critical importance of proper connections in historical buildings. A review of current literature yields little in terms of experimental and numerical data on the subject. Thus, there is an urgent need to study the behaviour of these connections. The present paper presents a series of tests carried out to characterize the wall-to-floor connections. Different specimens were constructed in laboratory to represent connections found in ‘Gaioleiro’ and Late ‘Pombalino’ buildings in downtown Lisbon. Pull-out tests of wall-to-floor connections were carried out on unstrengthened and strengthened specimens in order to study failure modes, maximum pullout forces, and corresponding displacements. These parameters allow better understanding of this type of connection and also the development of design recommendations for the strengthening.